The effects of different core stability training on trunk stability and athletic performance in adolescent female basketball players - Liang, I. J.; Lin, L. L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Trunk position is not only related to the performance of the physical fitness but important for the balance, stability and helping to progressively build fitness levels and improve athletic performance. This study aimed to investigate the effects of trunk stability and athletic performance after 2 types of core muscle training in adolescent female basketball players.